Deterministic mechanisms drive bacterial communities assembly in industrial wastewater treatment system. (October 2022) - Chen, Weidong; Wei, Jie; Su, Zhiguo; Wu, Linwei; Liu, Min; Huang, Xiaoxuan; Yao, Pengcheng; Wen, Donghui
Graphical abstract: Highlights: IWWTPs bacterial communities exhibited a clear species abundance distribution. Deterministic processes dominate IWWTPs bacterial communities assembly. Different IWWTPs harbor unique core bacterial community. IWWTP bacterial community was strongly linked to activated sludge function. Abstract: Microbial communities are responsible for biological treatment of many industrial wastewater, but our knowledge of their diversity, assembly patterns, and function is still poor. Here, we analyzed the bacterial communities of wastewater and activated sludge samples taken from 11 full-scale industrial wastewater treatment plants (IWWTPs) characterized by the same process design but different wastewater types and WWTP compartments. We found significantly different diversity and compositions of bacterial assemblages among distinct wastewater types and IWWTPs compartments. IWWTPs bacterial communities exhibited a clear species abundance distribution. The dispersal-driven process was weak in shaping IWWTP communities. Meanwhile, environmental and operating conditions were important factors in regulating the structure of the activated sludge community and pollutants removal, indicating that bacterial community was largely driven by deterministic mechanisms. The core microbial community in IWWTPs was different from that in municipal wastewater treatment plants (MWWTPs), and many taxa (e.g. the genus Citreitalea ) rarely were detected before, indicating IWWTPs harbored unique core bacterial communities. Furthermore, we found that bacterial community compositions were strongly linked to activated sludge function. These findings are important to both microbial ecologists and environmental engineers, who may optimize the operation strategies jointly for maintaining biodiversity, which in turn may promote a more stable performance of the IWWTP. Overall, our study enhances the mechanistic understanding of the IWWTP microbial community diversity, assembly patterns, and function, and provides important implications for microbial ecology and wastewater treatment processes.